2019
DOI: 10.1016/j.heliyon.2019.e02785
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs act as prognostic biomarkers in bladder carcinoma: A meta-analysis

Abstract: Background and purposeIncreasing studies have shown that different kinds of lncRNAs play key role in the development of multiple carcinomas. Therefore, we conducted a meta-analysis to investigate an association between the expression level of lncRNAs and the prognosis of bladder cancer (death or other clinical outcomes).MethodsA systematic literature search was performed by using PubMed. Twenty-four studies were included in the meta-analysis based on the inclusion and exclusion criteria. In total, there are 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…[19][20][21] Meanwhile, meta-analysis of several studies revealed that the expression levels of lncRNAs are associated with the prognosis of BC. 22 Increasing numbers of studies have reported that lncRNAs can serve as competing endogenous RNAs (ceRNAs) to bind miRNAs, consequently regulating the expression levels of downstream genes. 23,24 Some lncRNAs have been identified as molecular biomarkers for BC patients; however, novel correlated lncRNAs are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Meanwhile, meta-analysis of several studies revealed that the expression levels of lncRNAs are associated with the prognosis of BC. 22 Increasing numbers of studies have reported that lncRNAs can serve as competing endogenous RNAs (ceRNAs) to bind miRNAs, consequently regulating the expression levels of downstream genes. 23,24 Some lncRNAs have been identified as molecular biomarkers for BC patients; however, novel correlated lncRNAs are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers for early detection could be the most effective method of BlCa prevention, however the molecular mechanisms underlying BlCa progression are still not well characterized. Numerous publications have suggested that lncRNAs, such as UCA-1, MALAT1, PANDAR and so on, play key roles in development and progression of bladder cancer [4]. Nevertheless, their clinical use is still limited and none is yet validated or widely used in the clinical practice [5].…”
Section: Introductionmentioning
confidence: 99%
“…Bcl-2 overexpression in bladder cancer has been also reported to play an important role in cisplatin resistance ( Cho et al, 2006 ). The very first study by Zhong et al has shown atypical/aberrant expression of ncRNAs in bladder cancer might be exploited as bladder cancer biomarkers ( Zhong et al, 2019 ).…”
Section: Bladder Cancer and Non-coding Rnas (Ncrnas)mentioning
confidence: 99%